A high resolution 2D array detector system for small-field MRI-linac applications. (25th April 2018) - Gargett, Maegan; Oborn, Brad; Alnaghy, Sarah J; Causer, Trent; Petasecca, Marco; Rosenfeld, Anatoly B; Metcalfe, Peter
Abstract: A monolithic silicon small-field array detector is proposed for relative dosimetry applications in hybrid MRI-linac systems. The detector has high sampling resolution, with 512 active elements arranged with 2 mm pitch over a 46 mm × 46 mm detection area. Experimental measurements were performed in a custom-designed permanent magnet device that is compatible with a standard clinical linear accelerator. It can be configured in both inline and perpendicular magnetic-field-to-photon-beam orientations and produces magnetic field strengths 0.95 T and 1.20 T, respectively. Monte Carlo simulation data, obtained using the GEANT4 toolkit, are presented to supplement experimental data. Beam profiles show agreement to EBT3 film within 0.5 mm for FWHM and penumbral width measurement of small square fields (width ranging from 0.75 cm to 2.25 cm), in both inline and perpendicular magnetic field orientations. The detector can be used to accurately resolve normalised beam profiles in magnetic fields. The impact of electron return effects (ERE) in a small air gap surrounding the detector was also quantified. For the perpendicular orientation, a reduced profile intensity was observed for an increasing air gap width above the detector (10% at 2 mm) due to ERE. In the inline orientation, a very small increase in response relative to the zero field case was observed with an air gap above the detector (2% at 2 mm). Calibration of the device in a magnetic field will therefore be necessary; the zero field calibration is non-transferable. The MagicPlate-512 provides a high-resolution real time alternative to accurately measure normalised beam profiles in magnetic fields, and is expected to be a suitable array detector for use in magnetic field environments typical of MRI-linacs.